2011
DOI: 10.1179/1364859411y.0000000030
|View full text |Cite
|
Sign up to set email alerts
|

Quality of chloroquine tablets available in Africa

Abstract: Malaria is the biggest killer of African children, yet it is cheaply preventable and curable with insecticides spraying, impregnated bednets and effective drugs. This study aimed to evaluate the quality of Chloroquine (CQ) tablets available in selected African countries. Twenty-six samples of antimalarial CQ tablet of 100, 150 and 250 mg were collected from 12 African countries and evaluated for their quality in the Drugs Quality Control Laboratory of Rabat, Morocco. The identification and dosage of active pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…Gabon is a high-endemicity country for malaria [ 14 16 ]. A study in 2011, assessing the quality of chloroquine tablets in 12 African countries collected two chloroquine samples from the capital of Gabon (Libreville), which were both of good quality [ 17 ]. The World Health Organization (WHO) investigation in 2003 collected 25 chloroquine samples (29% poor-quality) and ten sulfadoxine-pyrimethamine samples (100% good quality) from pharmacies in Libreville.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gabon is a high-endemicity country for malaria [ 14 16 ]. A study in 2011, assessing the quality of chloroquine tablets in 12 African countries collected two chloroquine samples from the capital of Gabon (Libreville), which were both of good quality [ 17 ]. The World Health Organization (WHO) investigation in 2003 collected 25 chloroquine samples (29% poor-quality) and ten sulfadoxine-pyrimethamine samples (100% good quality) from pharmacies in Libreville.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) investigation in 2003 collected 25 chloroquine samples (29% poor-quality) and ten sulfadoxine-pyrimethamine samples (100% good quality) from pharmacies in Libreville. A limited number of reports are available from neighbouring countries Cameroon [ 5 , 17 – 22 ], Equatorial Guinea [ 23 ] and the Republic of Congo [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that all the batches except AVICQ met the pharmacopeial requirement of ≥75% chloroquine release in 45 min. [ 66 67 68 69 ] An assessment of the quality of a new formulation of chloroquine phosphate (A-CQ 100) submitted to the Medicine Evaluation Board, Netherlands for marketing approval reported that the amount of drug released (Q) from the innovator product (Nivaquine ® ) was of the order: 80% < Q < 100% within 30 min in dissolution media of pH values 1.2, 4.5, and 6.4. [ 68 ] The commercial product (comparator) that was used in this study released up to 103% in 30 min, a performance that is better than that reported for the innovator product, although the medium used in this study was distilled water.…”
Section: Resultsmentioning
confidence: 99%
“…Africa focused studies that intended to investigate the quality of chloroquine tablets found in African countries showed that percentage failures in dissolution ranged from 5% to 50%, in ingredient content from 20% to 67%, in disintegration was 20%, in crushing strength was 30%, and friability test was 21%. [19][20][21] Another commonly prescribed drug for malaria in Ethiopia is quinine. Quinine contains in its structure a quinoline nucleus and an amino alcohol side chain.…”
Section: Introductionmentioning
confidence: 99%